Presupposition Analysis in How to Train Your Dragon: Race to the Edge Film - Samosir, Tiondina; Simanjuntak, Naomi; Sihotang, Tiodor; Sirait, Tiofanny Elisabet; Hutabarat, Novra Melisa P. (Journal of English Language and Education, 2025)
This study investigates the types of presupposition found in the animated series How to Train Your Dragon: Race to the Edge, using George Yule’s (1996) classification as a theoretical framework. Understanding presupposition—implied meaning that underlies spoken or written expressions—is essential to developing pragmatic competence in language. Through a descriptive qualitative method, this research identifies and categorizes presuppositional triggers in the film’s dialogues, aiming to reveal how implicit meanings contribute to the narrative and character development. A total of 28 utterances containing presuppositions were analyzed, and all six types identified by Yule were found: existential, factive, lexical, structural, non-factive, and counterfactual. Among these, existential presuppositions were the most frequently occurring, representing 25% of the data. Factive, lexical, and structural presuppositions followed, each comprising 17.8%, while non-factive and counterfactual presuppositions were the least common, each at 10.7%. These results highlight the significant presence of presuppositional meaning in animated film dialogue, indicating that such media can be rich sources for examining pragmatic elements in language use. The findings suggest that presupposition not only enriches character interaction and emotional depth but also supports narrative cohesion. This research emphasizes the pedagogical potential of animated content in teaching pragmatic concepts and encourages further exploration of presupposition across different genres, audiences, and communicative contexts.